A Case of Successful Pregnancy Outcome with a Large Ovarian Cyst- A Case Report (Pulse, 2017)
Ovarian cysts during pregnancy are not uncommon. With increasing use of early antenatal ultrasound, the incidental discovery of adnexal masses during early gestation is a clinically relevant problem that requires careful consideration. Here, we have presented a case in pregnancy with a large ovarian cyst with a history of unilateral oophorectomy in pre-pregnancy state due to complex ovarian mass. She is a case of 26 years old prirnigravid, presented at 8 weeks of gestation with clinical and ultasonographic detection of a large cyst (about 9.2cm x 6.9cm) in the left ovary with suspicion of dermoid cyst. She had a history of right sided oophorectomy due to complex ovarian cyst at her 18 years of age which was histologically proved to be benign. This patient was treated conservatively with relevant investigation and tumour markers which was found insignificant with an aim to continue pregnancy until at least 14 weeks of gestation and was vigilant enough for early detection of any complication. Operative interference was not done at this stage due to increased chance of early fetal loss & clinically benign nature of the tumour. The tumour was persisting and gradually increasing in nature and at 11 weeks gestation it was about 11cm x 10om, suggestive of dermoid. Although clinically stable, with a fairly large ovarian cyst which was increasing in size & with a suspicion of filture torsion that will damage the only persisting ovary, this patient underwent laparotomy followed by ovarian cystectomy at 15 weeks of gestation. Close monitoring of the rest of the pregnancy period was done & it was uneventful except at 32 weeks of gestation she developed PIH which was managed conservatively. She underwent caesarean section at 38 weeks of gestation due to fetal distress.Pulse Vol.9 January-December 2016 p.49-53